Fraud Pada PT BTPN Syariah di Indonesia - saadah, salamatus (Jurnal Ilmiah Ekonomi Islam, 2024)
.BTPN syariah business in Indonesia is a business that offers promises for the protection of the insured as outlined in the Banking. In this study, it aims to determine the cause of fraud or the inability of PT BTPN Syariah to pay and regulate the running of the company as agreed in the banking policy. This research method is qualitative research using a literature review in the form of data or information obtained by the author by looking at the case study of BTPN Syariah fraut who has experienced fraud. The results of this study show that insurance companies that experience fraud or failure to keep promises according to the agreements made by PT BTPN Syariah to officers, company employees and customers listed in PT BTPN Syariah fraut regulations are caused by the lack of government supervision of PT Btpn Syariah companies, and the absence of good ethics from the management of PT BTPN Syariah companies, especially the owners of the company itself.